PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMIK PADA KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SD NEGERI MAEKARSARI 2 RAJEG - Ananda Sinta Ramadhan; Erdhita Oktrifianty; Dilla Fadhillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop comic-based learning media to enhance the reading comprehension skill of fourth-grade elementary school students. The background of this research is based on the low interest in reading and students’ difficulties in understanding reading materials. The development of media follows the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The learning media underwent trials involving a subject matter expert, media expert, classroom teacher, and fourth-grade students. The instruments used in this study included expert validation sheets and response questionnaires for teachers and students. Validation resultsfrom the subject matter and media expert showed that the developed comic media falls under the “Highly Appropriate” category, with percentages 91,1% and 94%, respectively. A limited trial with students showed that the comic media can halp improve students’ reading comprehensions, with the average results falling into the “Good” category. Therefore, the developed comic-based learning media is considered appropriate and can be used as an alternative medium for teacher reading comprehension in elementary schools.